2021
DOI: 10.1371/journal.pone.0258040
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of obstructive sleep apnea using Belun Sleep Platform wearable with neural network-based algorithm and its combined use with STOP-Bang questionnaire

Abstract: Many wearables allow physiological data acquisition in sleep and enable clinicians to assess sleep outside of sleep labs. Belun Sleep Platform (BSP) is a novel neural network-based home sleep apnea testing system utilizing a wearable ring device to detect obstructive sleep apnea (OSA). The objective of the study is to assess the performance of BSP for the evaluation of OSA. Subjects who take heart rate-affecting medications and those with non-arrhythmic comorbidities were included in this cohort. Polysomnograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Using an AHI at least 15 events/h to diagnose OSA, the sensitivity, specificity, positive predictive value, and negative predictive value of the Belum Sleep Platform were found to be 85, 87, 88, and 83%, respectively [11]. In the second study, which included 78 patients (African–American 53%, Asian 38%) referred from a sleep laboratory for suspected OSA, the corresponding values were 93, 74, 68, and 95% [12]. These values are similar to our findings (95.7, 77.6, 85.3, and 93.8%, respectively) in 129 Asian individuals with hypertension and high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using an AHI at least 15 events/h to diagnose OSA, the sensitivity, specificity, positive predictive value, and negative predictive value of the Belum Sleep Platform were found to be 85, 87, 88, and 83%, respectively [11]. In the second study, which included 78 patients (African–American 53%, Asian 38%) referred from a sleep laboratory for suspected OSA, the corresponding values were 93, 74, 68, and 95% [12]. These values are similar to our findings (95.7, 77.6, 85.3, and 93.8%, respectively) in 129 Asian individuals with hypertension and high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 97%
“…A proof-of-concept study has revealed close agreement between the apnea-hypopnea indexes (AHIs) from the Belun Ring and PSG in 50 participants without significant comorbidity [11]. A subsequent cohort study that included 78 patients referred by sleep physicians for suspected OSA reported similar results [12]. In this study, we aimed to evaluate the applicability of the Belun Sleep Platform in real-world patients with hypertension and high cardiovascular risk.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Penggunaan Cloud Computing dapat pula digunakan sebagai pendeteksi Obstructive Sleep Apnea (OSA). Penelitian (13) Memanfaatkan sensor yang digabungkan dalam bentuk perangkat wearable yang dapat dipakai oleh setiap individu untuk mengetahui dalam beberapa detik apakah orang tersebut sehat atau diragukan membawa penyakit. Perangkat medis yang digunakan terdiri dari sensor yang dapat dikomposisikan untuk memantau dari jarak jauh dan secara real-time status kesehatan mereka yang memiliki gejala virus corona atau mereka yang terinfeksi.…”
Section: Pembahasanunclassified
“…Yeh et al[44], 2021 N/A Fedorin and Slyusarenko[36], 2021 N/A Xu et al[22], 2022 a Indicates low risk of bias.b Indicates unclear risk of bias. c N/A: not applicable.d Indicates high risk of bias.…”
mentioning
confidence: 99%